Human exposure to early morning Anopheles funestus biting behavior and personal protection provided by long-lasting insecticidal nets. - Nicolas Moiroux; Georgia B Damien; Marc Egrot; Armel Djenontin; Fabrice Chandre; Vincent Corbel; Gerry F Killeen; Cédric Pennetier (PLoS ONE, 2014)
A shift towards early morning biting behavior of the major malaria vector Anopheles funestus have been observed in two villages in south Benin following distribution of long-lasting insecticidal nets (LLINs), but the impact of these changes on the personal protection efficacy of LLINs was not evaluated. Data from human and An. funestus behavioral surveys were used to measure the human exposure to An. funestus bites through previously described mathematical models. We estimated the personal protection efficacy provided by LLINs and the proportions of exposure to bite occurring indoors and/or in the early morning. Average personal protection provided by using of LLIN was high (≥80% of the total exposure to bite), but for LLIN users, a large part of remaining exposure occurred outdoors (45.1% in Tokoli-V and 68.7% in Lokohoué) and/or in the early morning (38.5% in Tokoli-V and 69.4% in Lokohoué). This study highlights the crucial role of LLIN use and the possible need to develop new vector control strategies targeting malaria vectors with outdoor and early morning biting behavior. This multidisciplinary approach that supplements entomology with social science and mathematical modeling illustrates just how important it is to assess where and when humans are actually exposed to malaria vectors before vector control program managers, policy-makers and funders conclude what entomological observations imply.